2008
DOI: 10.1007/s10865-008-9163-6
|View full text |Cite
|
Sign up to set email alerts
|

Social influence and pain response in women and men

Abstract: The purpose of this study was to examine the effects of social influence on responses to acute pain in women and men in a randomized experimental design. Sixty-eight undergraduates (32 women; 36 men) were randomly assigned to perform a cold pressor task either alone or in the presence of a same-sex friend. Expressions of pain were assessed with the short form of the McGill Pain Questionnaire. Overall social support was measured using the Krause social support assessment scale. The presence of a same-sex friend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
51
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 38 publications
4
51
1
1
Order By: Relevance
“…Other studies have shown that specific types of social support are helpful for specific stress reduction strategies (Olstad, Sexton, & Søgaard, in 2001;McClelland & McCubbin, 2008), and sufficient quantities of social support can reduce the effect of stress (Kinicki & McKee, 1996;McClelland & McCubbin, 2008). In addition, social support can improve a person's mental health in general (LaRocco, House, & French, 1980;McClelland & McCubbin, 2008).…”
Section: Perceived Social Supportmentioning
confidence: 99%
See 4 more Smart Citations
“…Other studies have shown that specific types of social support are helpful for specific stress reduction strategies (Olstad, Sexton, & Søgaard, in 2001;McClelland & McCubbin, 2008), and sufficient quantities of social support can reduce the effect of stress (Kinicki & McKee, 1996;McClelland & McCubbin, 2008). In addition, social support can improve a person's mental health in general (LaRocco, House, & French, 1980;McClelland & McCubbin, 2008).…”
Section: Perceived Social Supportmentioning
confidence: 99%
“…Social support can take the form of informative support, emotional support and/ or instrumental support (McClelland & McCubbin, 2008). Informative support includes advice, recommendations, and problem solving techniques; emotional support includes assistance in times of stress and difficulty, increasing self-esteem and motivation; and instrumental support includes physical or tactile support, such as specific forms of physical assistance (Cutrona & Russell, 1990;Warwick, Joseph Cordl, & Ashworth, 2004).…”
Section: Perceived Social Supportmentioning
confidence: 99%
See 3 more Smart Citations